SUPERVISION OF TRADITIONAL MEDICINES CONTAINING UNDECLARED SUBSTANCE: ANALYSIS OF INDONESIAN FDA MONITORING DATA FOR 2012 - 2021 - Dianasari, Widha; Nadjib, Mardiati (UI Scholars Hub, 2022)
Background: At a time when people believe in the efficacy and minimal risk of traditional medicines, government agencies that oversee traditional medicines often find chemicals that are intentionally added to traditional medicines. The purpose of this study is to present the findings of Undeclared Substance that have been added to traditional medicines for ten years, to analyze their relevance to the real situation related to diseases or health problems in Indonesia, and to examine the violations of related policies. Methods: This study used an observational design based on quantitative and qualitative data and analyzed descriptively. Quantitative data based on Traditional Medicines Monitoring data are published through the website (www.pom.go.id) in the category of public warning OT-BKO in 2012-2021. Further analysis, conducted in-depth interviews to explore the root cause of the problem at the level of policy makers. Documents and literature review were conducted to analyze the findings. Interviews with policy makers were also conducted to confirm findings and explore problems that were not obtained from documents and literature. Results: For ten years, Paracetamol was the most common type of Undeclared Substance found every year in traditional medicines. This is relevant to the high number of complaints related to indications for the use of Paracetamol, both from reports from health facilities and results from household surveys. Meanwhile, the findings of the Ephedrine Undeclared Substance - with indications for reducing respiratory disorders - only appeared in 2021. These findings are not only relevant to the COVID-19 pandemic and the entry of traditional medicines from foreign aid, which also contain Ephedra sinica. The Undeclared Substance' findings are inconsistent with the objectives of a number of regulations ranging from those related to traditional medicine to consumer protection. Conclusion: The findings of Undeclared Substance on traditional medicine were relevant to public health problems at that time. The emergence of traditional medicines with Ephedra shows that domestic producers do not understand the safety of traditional medicines. In addition, the existing policies and violations of these policies have not been understood by traditional medicine manufacturers.